Virtual Immersive Models for Viewing Social Science Fiction in European Cinema (diségno, 2018)
The paper illustrates the scientific assumptions and the results of a didactic activity aimed to explore the potential of interactiveand immersive dynamic perspectives by experimenting with new virtual reality applications for the enhancement of culturalheritage. In particular the study focuses on the enhancement of some European sociological science fiction movies. In this sense,immersive virtual reality, experimentally, has been used to realize and explore models capable of representing the quality of thespace and emotional conditions present in the selected movies.
Keywords: Interactive Walkthrough; 3D model; Sci-Fi movies